Fabrication and evaluation of poloxamer-facilitated, glyceryl monooleate-based tizanidine cubosomes - Hasan, Milad Jawad; Rajab, Nawal Ayash (Pharmakeftiki, 2025)
Cubosomes are lipid-based, nanostructured aqueous dispersions formed through a highly organized, spontaneous self-assembly process. These dosage forms have demonstrated potential as effective drug carriers, enhancing therapeutic efficacy. In this study, cubosomes were developed in order to evaluate their suitability as nanocarriers for the transdermal delivery of tizanidine (TZN); a skeletal muscle relaxant with low oral bioavailability. Cubosomal vesicles were prepared through the thin-film hydration technique, by using glyceryl monooleate (GMO) as the lipid component and poloxamer 407 (P407) as the stabilizer. Vesicle properties were modulated by varying the surfactant-to-lipid ratio. The developed TZN-loaded cubosomes were characterized for vesicle size (113.5–182.6 nm), polydispersity index (0.049–0.301), and drug entrapment efficiency (41.39%–79.20%). The results indicate that TZN-loaded cubosomal dispersions may represent a promising approach to transdermal drug delivery.